2002
DOI: 10.1093/ajcn/75.4.689
|View full text |Cite
|
Sign up to set email alerts
|

Intakes of energy and macronutrients and the risk of benign prostatic hyperplasia

Abstract: We observed modest direct associations between BPH and intakes of total energy, protein, and specific long-chain polyunsaturated fatty acids. Because eicosapentaenoic, docosahexaenoic, and arachidonic acids are highly unsaturated fatty acids, our findings support a possible role of oxidative stress in the etiology of BPH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
74
1
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(93 citation statements)
references
References 35 publications
12
74
1
6
Order By: Relevance
“…The results of the present study indicate that lifestyle that is, diet and exercise, is an important factor that supports the epidemiological data reporting that BPH is related to the intake of calories, protein and polyunsaturated fatty acids and inversely to the intake of fruits and vegetables. [7][8][9] In 1998, Hammarsten et al 10 reported that BPH patients share the same metabolic abnormalities of defective insulin-mediated glucose uptake and secondary hyperinsulinemia as patients with the metabolic syndrome, and suggested that BPH is another facet of the metabolic syndrome. Despite the fact that their patients with BPH had many of the metabolic abnormalities of the metabolic syndrome, they suggested that hyperinsulinemia might be a causal factor in the development of BPH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the present study indicate that lifestyle that is, diet and exercise, is an important factor that supports the epidemiological data reporting that BPH is related to the intake of calories, protein and polyunsaturated fatty acids and inversely to the intake of fruits and vegetables. [7][8][9] In 1998, Hammarsten et al 10 reported that BPH patients share the same metabolic abnormalities of defective insulin-mediated glucose uptake and secondary hyperinsulinemia as patients with the metabolic syndrome, and suggested that BPH is another facet of the metabolic syndrome. Despite the fact that their patients with BPH had many of the metabolic abnormalities of the metabolic syndrome, they suggested that hyperinsulinemia might be a causal factor in the development of BPH.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies report increased risk for BPH associated with high intake of calories, protein and longchain polyunsaturated fatty acids. 7,8 Inverse associations have been reported for consumption of fruits and vegetables. 7,9 Recently it has been suggested that hyperinsulinemia may be involved in the development of BPH and that it is an aspect of the metabolic syndrome, along with other common health problems including PCa.…”
Section: Introductionmentioning
confidence: 99%
“…2 This was confirmed in a later study that found no association between energyadjusted total fat intake and BPH in 33 344 healthy aging men. 22 Studies comparing anthropometric and biochemical covariates in patients with PC and BPH, respectively, are limited. Metabolic parameters including fasting plasma glucose, lipid profile and clinical parameters such as BMI and waist-to-hip ratio were similar in patients with PC and BPH in a recent study.…”
Section: Introductionmentioning
confidence: 99%
“…W literaturze opisana jest rola nawyków żywieniowych na rozwój raka prostaty [6,7,8] oraz BPH [4,5]. Nieliczne są publikacje określające związek diety ze stężeniem hormonów wpływających na etiologię BPH, natomiast wnioski z tych badań są często kontrowersyjne [5,9,10].…”
Section: Wstępunclassified
“…W zdrowej diecie należy natomiast wyeliminować słodzone i gazowane napoje, bogate w cukry proste, kwas fosforowy (popularny napój gazowany) oraz chemiczne dodatki [10]. Nie wykazano zależności pomiędzy spożyciem słodkich napojów a stężeniem parametrów biochemicznych i hormonalnych u mężczyzn z BPH.…”
Section: Dyskusjaunclassified